SOSIALISASI SPGDT (ANALISIS SISTEM PENANGGULANGAN GAWAT DARURAT TERPADU) DI PUSKESMAS PURWAKARTA - Serly, Serly; Dina Hartini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The SPGDT program has not shown maximum results, so that many people complain about it when they need health services. Although in almost every city there are Emergency Departments of all types of hospitals, both government and private, ambulance services and various other health facilities, but integration in serving emergency patients has not been systematic, lack of good communication between health facilities and between health workers with the community. The purpose of this literature review is to explain the description of the SPGDT implementation and the factors that influence the running of the SPGDT. that influence the SPGDT program are standard operating procedures (SOPs) and resources. The results of the study found that SOPs in various regions were still not good at discussing SOPs and socialization to the community. The resources at the puskesmas are good in terms of budget but are still lacking in the human resources section because the implementing officers of the puskesmas unit have never been trained and have not yet obtained an emergency training certificate. the SPGDT program in various regions, it has not been able to meet central government standards in terms of response time, SOP, and resources.